Understanding the Multifaceted Role of Neutrophils in Cancer and Autoimmune Diseases - Wang, Xu; Qiu, Lin; Li, Ziyi; Wang, Xiang-Yang; Yi, Huanfa (Frontiers in Immunology, 2018)
Neutrophils are one of the first immune cell types that are recruited to injury and infection site. As a vital component of the immune system, neutrophils are heterogeneous immune cells known to have phagocytic property and function in inflammation. Recent studies revealed that neutrophils play dual roles in tumor initiation, development, and progression. The multifunctional roles of neutrophils in diseases are mainly due to their production of different effector molecules under different conditions. N1 and N2 neutrophils or high density neutrophils (HDNs) and low density neutrophils (LDNs) have been used to distinguish neutrophils subpopulations with pro- vs anti-tumor activity, respectively. Indeed, N1 and N2 neutrophils also represent immunostimulating and immunosuppressive subsets, respectively, in cancer. The emerging studies support their multifaceted roles in autoimmune diseases. Although such subsets are rarely identified in autoimmune diseases, some unique subsets of neutrophils, including low density granulocytes (LDGs) and CD177+ neutrophils, have been reported. Given the heterogeneity and functional plasticity of neutrophils, it is necessary to understand the phenotypical and functional features of neutrophils in disease status. In this article, we review the multifaceted activates of neutrophils in cancer and autoimmune diseases, which may support new classification of neutrophils to help understand their important functions in immune homeostasis and pathologies.